2019
DOI: 10.1111/jocs.14078
|View full text |Cite
|
Sign up to set email alerts
|

Repair of bileaflet prolapse in Barlow syndrome: The 4‐chord technique

Abstract: Barlow syndrome is a form of degenerative mitral valve (MV) disease found in a subset of patients with bileaflet prolapse. The hallmark of Barlow's disease includes excessive and billowing leaflet tissue caused by myxomatous tissue proliferation, elongated chordae, and pronounced annular dilatation. Surgical repair of patients with Barlow's disease is challenging due to the extent of the leaflet and annular abnormalities. Several techniques have been described to repair Barlow's MV including currently popular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…7 It is generally recommended to attach the artificial neo-chordae to the fibrous portion of the head of the papillary muscle to minimize injury to the muscle tissue. There are multiple stitching techniques that have been described to anchor the ePTFE neo-chordae to the papillary muscles 8 such using a simple nonknotted stitch, [9][10][11] a figureof-eight stitch, [12][13][14] a mattress stitch reinforced with a single unknotted pledget 15,16 and a mattress stitch reinforced with two pledgets knotted over the papillary muscle. [17][18][19][20] In vitro studies have shown that both the knotted mattress stitch with two pledgets and the figure-of-eight stitch provided adequate tensile strength within the limits of normal physiological range.…”
Section: Introductionmentioning
confidence: 99%
“…7 It is generally recommended to attach the artificial neo-chordae to the fibrous portion of the head of the papillary muscle to minimize injury to the muscle tissue. There are multiple stitching techniques that have been described to anchor the ePTFE neo-chordae to the papillary muscles 8 such using a simple nonknotted stitch, [9][10][11] a figureof-eight stitch, [12][13][14] a mattress stitch reinforced with a single unknotted pledget 15,16 and a mattress stitch reinforced with two pledgets knotted over the papillary muscle. [17][18][19][20] In vitro studies have shown that both the knotted mattress stitch with two pledgets and the figure-of-eight stitch provided adequate tensile strength within the limits of normal physiological range.…”
Section: Introductionmentioning
confidence: 99%